2018
DOI: 10.1038/s41598-018-34574-6
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Bone Metabolomics—Lipidomics Strategy for Pathological Mechanism of Postmenopausal Osteoporosis Mouse Model

Abstract: Osteoporosis, characterized by bone mass reduction and increased fractures, has become a global health problem that seriously affects the health of people, especially postmenopausal women; however, the current pathogenesis of postmenopausal osteoporosis (PMOP) has not been thoroughly elucidated to date. In this study, bilateral ovariectomy was performed to establish an OVX mouse model of osteoporosis. UPLC-Q-TOF-MS-based lipidomics in combination with metabolomics were used to analyze the femur tissue of osteo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
58
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(67 citation statements)
references
References 52 publications
8
58
0
Order By: Relevance
“…As is shown in Figure c, >80% of the RSD values (89.65% in the positive ion mode and 94.82% in the negative ion mode) of the QC samples were <20%. These results demonstrate that the stability of the proposed method was sufficient (Zhao et al, ). The entire normalized data from all samples were imported into SIMCA‐P program (version 11) to perform PCA and PLS‐DA.…”
Section: Resultssupporting
confidence: 53%
“…As is shown in Figure c, >80% of the RSD values (89.65% in the positive ion mode and 94.82% in the negative ion mode) of the QC samples were <20%. These results demonstrate that the stability of the proposed method was sufficient (Zhao et al, ). The entire normalized data from all samples were imported into SIMCA‐P program (version 11) to perform PCA and PLS‐DA.…”
Section: Resultssupporting
confidence: 53%
“…Recently, modern high-throughput technology including nuclear magnetic resonance spectroscopy (NMR), gas chromatography mass spectrometry (GC-MS), liquid chromatography mass spectrometry (LC-MS), or capillary electro-phoresis mass spectrometry (CE-MS) coupled with multivariate analysis was successfully performed multiparametric metabolic responses to pathophysiological and environmental perturbations in metabolomics research ( Sun et al, 2013b ; Zhang et al, 2017 ; Sun et al, 2019 ; Zhao et al, 2020 ). It has been widely used in early diagnosis, disease staging, and treatment evaluation of osteoporosis ( Lv et al, 2016 ; Zhao et al, 2018 ; Xia et al, 2019 ; Zhang et al, 2019 ; Ye et al, 2020 ). Animal model of OP can be set up by traditional castration surgery and modern study ( Tella and Gallagher, 2014 ; Drake et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…While HexCer d18:1/16:1 was increased in HDL and decreased in LDL, three other HexCer species (d18:1/22:0, d18:1/24:0, and d18:1/24:1) showed the exact opposite pattern. HexCer belongs to a group of glycosphingolipids which is considered to be essential in the formation of osteoblasts [38], and an increased level of glycosphingolipids can accelerate osteoblast differentiation, which may disturb the balance between bone resorption and formation in bone tissue [10]. Although the four HexCer species in this study showed different trends in both lipoproteins, the change in the total amount of HexCer in each lipoprotein fraction was negligible ( Figure S3) due to compositional alterations.…”
Section: Lipid Alterations In Each Lipoprotein From Patients With Pmopmentioning
confidence: 76%
“…A recent report on the aging-related lipidomic changes in human bone mesenchymal stem cells (BMSCs) showed that PC, PE, and Cer levels were significantly elevated with aging [33]. Cer levels were reported to be increased in the femur of a PMOp mouse model [10] and in the serum (Cer d18:0/18:0) of an ovariectomy-induced osteoporosis rat model [34]. These results are in line with the observed increase in most Cer species in patients with PMOp.…”
Section: Lipid Alterations In Each Lipoprotein From Patients With Pmopmentioning
confidence: 99%
See 1 more Smart Citation